Impact of subjective and objective neighbourhood characteristics and individual socioeconomic position on allostatic load: A cross-sectional analysis of an all-age UK household panel study. (November 2022) - Whitley, Elise; Olsen, Jonathan; Benzeval, Michaela
Abstract: Research suggests that individuals living in more disadvantaged neighbourhoods experience higher levels of stress but this has generally been based on self-reported stress. We used survey-based neighbourhood quality indicators and biomarker data from Understanding Society, linked to census and crime statistics to explore associations of allostatic load (AL), an objective biomarker-based measure of cumulative stress, with subjective and objective neighbourhood characteristics. Analyses of 6887 respondents living in England show greater AL among those living in more disadvantaged areas, with objective measure associations stronger than subjective. Neighbourhood inequalities in AL were lower among respondents with higher individual SEP. These results suggest that individual-level SEP mitigates against the impact of negative, particularly objective, neighbourhood characteristics. Policies to reduce health inequalities should consider both individual and neighbourhood circumstances. Highlights: Residents in more disadvantaged areas have greater objective stress levels. Associations with objective area measures are stronger than subjective. Individual socioeconomic position may mitigate area associations.